Intra-articular corticosteroid utilization and characterizations of use in juvenile idiopathic arthritis within the PR-COIN registry - Balay-Dustrude, Erin; Weiss, Jennifer E.; Goh, Y. Ingrid; Rubin, Nathan; Bullock, Danielle R. (Frontiers in Pediatrics, 2024)
Objective: Intra-articular corticosteroid injections (IACI) have been shown to be effective at improving arthritis across juvenile idiopathic arthritis (JIA) categories. The American College of Rheumatology (ACR) recommends IACI use as primary and adjunctive therapy for JIA patients. However, there remains minimal data describing actual IACI use in North America. The objective of this study was to describe and to evaluate IACI use in JIA, utilizing the Pediatric Rheumatology Care and Outcomes Improvement Network (PR-COIN) registry.Methods: Study participants from 13 sites were enrolled in the PR-COIN registry from 2011-2015. Demographic and clinical variables were summarized and Chi-squared and t-tests were used to evaluate differences between participants who did or did not receive IACI. Multiple logistic regression models were used to evaluate characteristics associated with IACI treatment.Results: Our study included 3,241 participants, the majority of whom were white (85%), female (71%) and had oligoarticular JIA (39%). IACI was administered at least once in 23% of participants, the majority of whom had oligoarticular disease (52.5%), but overall use in oligoarticular participants was low at 30.8%. IACI use varied significantly between treatment centers and use was associated with oligoarticular disease, ANA positivity, and use of other systemic medications.This study demonstrates that participants with JIA enrolled in the PR-COIN registry between 2011 -2015 with persistent oligoarticular disease, ANA positivity, and use of other systemic medications were more likely to receive IACI. However, IACI use was lower than expected for oligoarticular participants.